Comprehensive Mapping of EZ-Tn5 Transposon Insertion Sites in Pseudomonas argentinensis SA190 Using RATE-PCR - Büsra Elkatmis; Baoda Han; Sabiha Parween; Stanislav Kopriva; Heribert Hirt; Maged Saad (Bio-Protocol, 2025)
Transposon mutagenesis is a powerful tool for investigating gene function in bacteria, particularly in newly discovered species. In this study, we applied the hyperactive EZ-Tn5 transposase system to Pseudomonas argentinensis SA190, an endophytic bacterium known for enhancing plant resilience under drought stress. By leveraging the random amplification of transposon ends (RATE)-PCR method, we successfully mapped the insertion sites of the transposon within the SA190 genome. This approach enabled the precise identification of disrupted genes, offering insights into their roles in bacterial function and interaction with host plants. Our comprehensive protocol, including competent cell preparation, transformation, and insertion site mapping, provides a reliable framework for future studies aiming to explore gene function through mutagenesis.